2009
DOI: 10.1029/2008wr007018
|View full text |Cite
|
Sign up to set email alerts
|

More efficient optimization of long‐term water supply portfolios

Abstract: [1] The use of temporary transfers, such as options and leases, has grown as utilities attempt to meet increases in demand while reducing dependence on the expansion of costly infrastructure capacity (e.g., reservoirs). Earlier work has been done to construct optimal portfolios comprising firm capacity and transfers, using decision rules that determine the timing and volume of transfers. However, such work has only focused on the short-term (e.g., 1-year scenarios), which limits the utility of these planning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Leasing and adaptive options supply instruments can significantly lower water supply costs and improve reliability while enhancing the overall efficiency of alternatives (both logistically and volumetrically). The work confirmed the cost savings at high reliability suggested in prior studies [ Characklis et al , 2006; Kirsch et al , 2009]. Our “many‐objective” analysis shows that cost savings appeared even in portfolios that followed a more conservative water supply approach by using leases and options sparingly as a supplement to the city's permanent rights.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Leasing and adaptive options supply instruments can significantly lower water supply costs and improve reliability while enhancing the overall efficiency of alternatives (both logistically and volumetrically). The work confirmed the cost savings at high reliability suggested in prior studies [ Characklis et al , 2006; Kirsch et al , 2009]. Our “many‐objective” analysis shows that cost savings appeared even in portfolios that followed a more conservative water supply approach by using leases and options sparingly as a supplement to the city's permanent rights.…”
Section: Discussionsupporting
confidence: 85%
“…Table 2 shows that Case B adds the dropped transfers objective f dropped and the cost variability objective f costvar with an additional constraint on cost variability, c costvar . Prior work has shown that adding temporary transfers such as options and leases can reduce the city's supply cost while maintaining high reliability [ Characklis et al , 2006; Kirsch et al , 2009]. The purpose of this section is to provide a broader understanding of the cost effectiveness and efficiencies provided by the adaptive options contract.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations